1998
DOI: 10.1152/ajpregu.1998.274.6.r1536
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines inhibit growth in fetal sheep in the absence of hypoxemia

Abstract: To evaluate contributions of catecholamines to inhibition of growth during chronic hypoxemia or severe undernutrition, epinephrine (Epi; 0.25–0.35 μg ⋅ kg−1 ⋅ min−1) or norepinephrine (NE; 0.5–0.7 μg ⋅ kg−1 ⋅ min−1) was administered to normoxemic fetuses in twin-pregnant ewes for 8–12 days, from 125 to 127 days of gestation. Both had similar effects and decreased fetal weight by ∼20% relative to control twins ( P < 0.01). Weight gain ceased during infusion of Epi or NE (−21 ± 14.8 or 14 ± 20.9 g/day), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 14 publications
2
57
1
Order By: Relevance
“…The 55% increase in fetal plasma glucose concentrations is most likely due to reduced glucose oxidation in peripheral tissues of the NE fetus, which is further supported by the chronic hyperoxemia (3,39). Previous studies in fetal sheep have found that chronic hyperglycemia for 7-10 days results in impaired ␤-cell function and decreased insulin secretion (10).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The 55% increase in fetal plasma glucose concentrations is most likely due to reduced glucose oxidation in peripheral tissues of the NE fetus, which is further supported by the chronic hyperoxemia (3,39). Previous studies in fetal sheep have found that chronic hyperglycemia for 7-10 days results in impaired ␤-cell function and decreased insulin secretion (10).…”
Section: Discussionmentioning
confidence: 92%
“…During the 7-day infusion period, the dose of NE concentration was started at 1 g/min for the first 24 h, increased to 2 g/min for days 2-4, and finally increased to 4 g/min for days 5-7, as described previously (3). Control fetuses received an infusion of saline with 0.3% ascorbic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redistribution of blood flow during fetal stress is secondary to increased sympathoadrenal system activity and results in exaggerated elevations in plasma catecholamine levels [32,33] . This cascade of events is important in the pathophysiology of pregnancy disorders associated with placental dysfunction [34,35] , impaired placental blood flow and is a cause of intrauterine growth restriction [36][37][38] . This also explains the adverse effects on the fetus of uptake inhibitors, such as cocaine and amphetamines, which block catecholamine transport [6,39] .…”
Section: The Second Pathophysiology: Vasoconstrictive Mechanismsmentioning
confidence: 99%
“…Similarly, maternal sympathoadrenal dysregulation (i.e., elevated maternal norepinephrine levels) has been associated with low birthweight (4), and norepinephrine infusions induce uterine artery contractions and decrease uterine artery blood flow in humans (19,20). Furthermore, norepinephrine administered to pregnant ewes affects uterine artery and placental blood flow and decreases fetal insulin concentrations, increases fetal insulin-like growth factor binding protein 1 (IG-FBP-1) concentrations and results in fetal growth restriction (21,22). Although studies have been conducted to assess the effects of maternal HPA and sympathoadrenal function on fetal growth in animal models and birthweight and prematurity in humans, we are not aware of any studies that have assessed the effects of prenatal cortisol and norepinephrine on human fetal weight.…”
Section: Introductionmentioning
confidence: 99%